1985
DOI: 10.1002/clc.4960080612
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with diltiazem and propranolol: Precipitation of congestive heart failure

Abstract: Summary:Although congestive heart failure has been reported with the combination of a beta blocker and either verapamil or nifedipine, it has not previously been reported for combination therapy that includes diltiazem. The following case documents the occurrence of clinical congestive failure in a patient with baseline left ventricular dysfunction and severe angina pectoris. Although the patients had tolerated propranolol therapy for years without difficulty, and high-dose diltiazem monotherapy with an excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The combined treatment with β-blockers and calcium channel blockers has additive effects on heart rate, cardiac conduction and cardiac contractility. Cases have been documented on concurrent treatment with these two classes of drugs leading to congestive heart failure, hypotension, bradycardia or even cardiogenic shock [ 71 , 72 ]. We identified that potential DDIs were common when Clopidogrel was used with Pantoprazole, and when Clopidogrel was used with Atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…The combined treatment with β-blockers and calcium channel blockers has additive effects on heart rate, cardiac conduction and cardiac contractility. Cases have been documented on concurrent treatment with these two classes of drugs leading to congestive heart failure, hypotension, bradycardia or even cardiogenic shock [ 71 , 72 ]. We identified that potential DDIs were common when Clopidogrel was used with Pantoprazole, and when Clopidogrel was used with Atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to felodipine, calcium antagonists with no or low vascular selectivity have clinically important pharmacodynamic interactions with @-blockers, since both groups of drugs have significant inhibitory effects on cardiac contractility and conduction ( 3 3 1, 90,94,105,115). Additive cardiodepression resulting in severe conduction disturbances or heart failure has been reported with the combination of verapamil and a P-blocker (90,115).…”
Section: Pharmacokinetic and Pharmacodynamic Interactionsmentioning
confidence: 94%
“…Additive cardiodepression resulting in severe conduction disturbances or heart failure has been reported with the combination of verapamil and a P-blocker (90,115). Diltiazem also has significant negative inotropic and dromotropic effects and combination with a P-blocker may cause adverse cardiac effects (51,105). Even with nifedipine, which has a moderate degree of vascular selectivity and is generally well tolerated in combination with a @-blocker, there have been occasional reports of precipitation of heart failure (3, 94).…”
Section: Pharmacokinetic and Pharmacodynamic Interactionsmentioning
confidence: 98%
“…However, one patient who had tolerated each individual drug did develop congestive heart failure with the combination. This phenomenon has also been well documented by Strauss and coworkers [63].…”
Section: Chronic Stable Anginamentioning
confidence: 71%